Risk of Death in COVID-19 Patients with Comorbidity of Chronic Kidney Disease: Meta Analysis - Isna Nur Rohmah; Didik Gunawan Tamtomo; Bhisma Murti (Masters Program in Public Health, 2021)
Background: Coronavirus disease 2019 or known as COVID-19 was a disease caused by severe acute respiratory coronavirus 2 (SARS-CoV-2). There are seven comorbidities that experience the most severity and death when infected with COVID-19, namely hypertension, diabetes mellitus, cardiovascular disease, chronic obstructive pulmonary disease, chronic kidney disease, cerebrovascular disease, and cancer. This study aimed to estimate the magnitude of the risk of death in COVID-19 patients with comorbid chronic kidney disease, with a meta-analysis of primary studies conducted by previous authors.Subjects and Method: This study was a systematic review and meta-analysis with the following PICO, population: COVID-19 patients. Intervention: comorbid chronic kidney disease. Compa